Student Internship Information Management System at the Aceh Government's Department of Manpower and Population Mobility - Rahmi, Tutia; Imilda (Journal Dekstop Application (JDA), 2023)
In the current digital age, local governments are increasingly prioritizing efficiency and effectiveness in data and information management. However, the Department of Manpower and Population Mobility of the Aceh Government continues to face challenges in delivering thorough information services, particularly concerning student internship data. The research aims to address these issues by designing and implementing a Student Internship Data Management Information System within the department. The study focuses on enhancing internship data management processes, which currently rely on time-consuming manual systems. Through problem identification and automated information system solution development, the research incorporates user needs analysis and system testing to ensure reliability and functionality. Results indicate that the new system implementation will significantly benefit users by improving data management efficiency and enabling faster, more accurate access to relevant information